STUDI KOMPARATIF HEADWAY DAN METODE PEMBAYARAN PADA MRT JAKARTA JALUR LINTAS UTARA – SELATAN DAN MRT BANGKOK JALUR BIRU - Rahmawati, Roselina; Rahman, Yusuf Noufal; Hidayati, Alfiyana; Khozinunniam, Khozinunniam; Atmaja, Ilman (Construction and Material Journal, 2025)
The ongoing process of increasing urbanization has resulted in substantial growth in the urban population—a phenomenon that is particularly evident in major cities such as Jakarta and Bangkok, which have the largest populations in Southeast Asia. The rapid population growth in these cities has created a pressing need for efficient transportation systems. The MRT (Integrated Transportation Mode) is poised to address these challenges by enhancing mobility. This study undertakes a comparative analysis of the operational performance of the Jakarta MRT and the Bangkok MRT, with a particular focus on headway and payment methods. The research method employed was descriptive quantitative with a comparative approach, wherein data was obtained through a literature study and documentation from secondary sources, including official reports and previous research. The main variables compared were headway, which shows how well the service is working, and payment method, which shows how easy it is for passengers to make transactions. The results of the study indicate that the Bangkok MRT exhibits shorter headways compared to the Jakarta MRT. The temporal compression of the service interval is indicative of its efficacy. In terms of payment methods, the Bangkok MRT's flexibility in offering various options provides a clear advantage in terms of convenience for foreign users, while the Jakarta MRT continues to prioritize the convenience of local users.